Role of Oxide Reducibility in the Deoxygenation of Phenol on Ruthenium Clusters Supported on the Anatase Titania (1 0 1) Surface - Chen, Hsin-Yi Tiffany; Pacchioni, Gianfranco (ChemCatChem, 2016)
The deoxygenation of phenol on stoichiometric and reduced Ru10/TiO2 anatase (1 0 1) surfaces has been studied by using DFT with the Hubbard correction (DFT+U). If the molecule orients with the OH group towards the metal–oxide interface, the direct deoxygenation of phenol can occur. However, on the stoichiometric TiO2 surface, the reaction is thermodynamically unfavorable. Two kinds of reduced surfaces have been considered: one in which Ti3+ centers are generated by hydrogen addition, and a second one in which a water molecule is removed from a hydroxylated surface with the formation of O vacancies and Ti3+ centers. On the surface reduced by hydrogen addition (Ti3+ ions), the phenol molecular and dissociative adsorptions (C6H5+OH fragments) become isoenergetic; the barrier to dissociate the C−OH bond is 1.19 eV, which indicates a possible channel for the deoxygenation of phenol. On the surface reduced by O vacancies, the dissociative adsorption is 0.22 eV more stable than the molecular adsorption, which indicates a thermodynamically favorable process; however, the C−OH activation energy is higher, 1.50 eV. The results show that the C−O scission can be an important step towards the direct deoxygenation. The reduction of the surface facilitates the direct deoxygenation of phenol significantly. Stoichiometric versus reduced surfaces: Reduced Ru10/TiO2 surfaces can help the occurrence of phenol direct deoxygenation by facilitating C−OH cleavage.